Wireless Data Acquisition System - Biradar, Shubhangi R; Bhuyar, Devendra L (International Journal of Computer Sciences and Engineering, 2019)
In steel and metal industries the temperature factor is very important, as it defines the quality of the product used. Minute change in temperature can affect the product thus causing faulty or defective product. So we must design a wireless facts acquisition system to measure correct temperature up to at least one degree Celsius and for you to preserve in around seven-hundred degree Celsius. So all sensors and components need to be chosen as a considerably. Here the product details are saved in a computer at the server end. The wireless statistics acquired on the receiving quit, may be displayed on 7 segment display same facts need to be logged in to laptop software program with time to devise the graph on the equal time. Also buzzer will sound if any severe condition takes place. The product layout of the machine must be carried out to face up to circuit in seven hundred degree Celsius environment.